Study of stress, anxiety, depression and coping strategies among nursing students in a tertiary care teaching hospital, South India - Das, Biranchi Narayan; Mohandas, Anu; Syed, Saba (International Journal Of Community Medicine And Public Health, 2021)
Background: Nursing students are at extremely high risk for experiencing stress, anxiety, and depression due to their varied circumstances. Indian studies has revealed, moderate stress among 77-82% of nursing students. The better the nursing students can manage their stress and anxiety and adopt healthy coping strategy, the more successful they can be in their clinical training and academic performance. Objective of the current study was to estimate the prevalence of depression, anxiety, and stress among the BSc nursing students and its association with socio-demographic and academic factors and to find the coping strategies adopted by them. Methods: A cross sectional study was conducted among 149BSc nursing students in a teaching hospital in Hyderabad. The data was collected by pre-validated questionnaire with 3 parts. Part I: socio-demographic and academic parameters, part II: psychological information (DASS-21) and part III: coping strategies (brief COPE). Data was analysed using SPSS version 24.The percentages of stress, anxiety and depression was found and categorised to mild, moderate, severe and extremely severe and associations analyzed with Chi-square test. The mean score and percentages were calculated for coping strategies. Results: The mean age of nursing students was 20±1.6 years. The proportion having depression, anxiety and stress were 67.7%, 85.3% and 46.9% respectively. The coping strategies ‘used a lot’ were spirituality (43.6%), Information support (30.9%) and active coping (28.2%). The study showed depression (p=0.05) and stress (p=0.002) to be higher among 2nd and 4th year students. Lack of leisure time (p=0.036) and difficulty in academics (p= 0.017) were identified as stressors. Conclusions: This study noted high levels of psychological disturbances among nursing students. There is urgent need to plan stress management programmes with peer instructors, mentorship, more leisure and outdoor learning activities.